The Level of Organizational Power Among Educational Zone Managers in the Capital Secretariat - Sana’a: from the Administrative Employees’ Perspective - Sultan, Youssef Qaid (Journal of Educational and Psychological Sciences, 2025)
This study aimed to assess the level of organizational power among educational district directors in the Capital Secretariat - Sana’a, from the perspective of administrative employees, and to determine whether statistically significant differences (at α ≤ 0.05) exist between the mean responses concerning organizational power based on variables: gender, job title, academic qualification, and years of experience. The researcher employed a descriptive analytical approach and used a questionnaire to collect data from a stratified random sample of 201 employees. Results showed that the overall organizational power level among district directors was moderate, with a mean score of 3.12 out of 5, and varied across different dimensions, ranked as follows: formal position power (mean = 4.11, high), coercive power (mean = 3.73, high), personal power (mean = 3.58, high), expert power (mean = 3.15, moderate), informational power (mean = 2.10, low), and reward power (mean = 2.07, low). No statistically significant differences were found in organizational power perceptions related to gender, job title, academic qualification, or years of experience at α ≤ 0.05. The study recommends leadership development through specialized training, experience sharing, and fostering an empowerment culture to enhance institutional performance.